2018
DOI: 10.1371/journal.pone.0206438
|View full text |Cite
|
Sign up to set email alerts
|

Assessing men with erectile dysfunction before and after living donor liver transplantation in real-world practice: Integrating laboratories into clinical settings

Abstract: ObjectiveTo evaluate the predictive role of the Model for End-Stage Liver Disease (MELD) score concerning changes in testosterone levels following living donor liver transplantation (LDLT) and the effects of LDLT on total testosterone and sex hormone-binding globulin (SHBG) levels, the free androgen index (FAI) and erectile function in LDLT recipients.Participants41 adult male recipients of LDLT were evaluated before transplantation and six months after LDLT.Main outcome measuresWe evaluated the effects of LDL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…[268] Nonpharmacological treatments, including sex therapy or vacuum devices, have not been tried in patients with cirrhosis, but may be a safe alternative. [269] Furthermore, a small study found that sexual satisfaction and erectile dysfunction improved after LT. [257,260] More research is needed to determine how to manage sexual dysfunction in this population, particularly among women.…”
Section: Sexual Dysfunctionmentioning
confidence: 99%
“…[268] Nonpharmacological treatments, including sex therapy or vacuum devices, have not been tried in patients with cirrhosis, but may be a safe alternative. [269] Furthermore, a small study found that sexual satisfaction and erectile dysfunction improved after LT. [257,260] More research is needed to determine how to manage sexual dysfunction in this population, particularly among women.…”
Section: Sexual Dysfunctionmentioning
confidence: 99%
“…It is important, since male patients suffering from end-stage of liver disease exhibit worse sexual function which is mirrored in hypogonadism and feminization. Among others, in these patients, testicular atrophy, decreased T level, reduced secondary sexual characteristics, muscle reduction, gynecomastia, decreased libido and fertility are frequently reported [ 24 , 30 ]. According to the latest reports, almost 50% of men with diagnosed cirrhosis, reduced spermatogenesis and peritubular fibrosis are noticed [ 33 ].…”
Section: Liver Transplant Recipientsmentioning
confidence: 99%
“…According to the latest reports, almost 50% of men with diagnosed cirrhosis, reduced spermatogenesis and peritubular fibrosis are noticed [ 33 ]. All the aforementioned symptoms may result in a regressed quality of professional, social and sexual life leading to high fatigue levels, depression or impotence [ 30 ]. Successful liver transplantation primarily saves the lives of patients suffering from end-stage liver disease but, secondly, it should improve the life quality of liver transplant recipients, among others, by restoring hormonal balance.…”
Section: Liver Transplant Recipientsmentioning
confidence: 99%
See 2 more Smart Citations